Why are american billionaires buying up ruined newspapers? - I S Pilshchikov (RUDN Journal of Studies in Literature and Journalism, 2014)
The author of this article tries to analyze the reasons why billionaires in the United States are buying up loss making newspapers. А growing number of traditional media outlets are struggling to find new audience in the era of the Internet. Under the circumstances it appears even more extraordinary that the American billionaires are investing into the ruining newspapers.